Anisotropic domain switching in Pb(Mg1/3Nb2/3)O3‐0.30PbTiO3 single crystals with rhombohedral structure. Issue 7 (14th February 2018) - Zhou, Yaming; Li, Qiang; Xu, Chao; Zhuo, Fangping; Yan, Qingfeng; Zhang, Yiling; Chu, Xiangcheng
Abstract: Anisotropic domain switching paths in [001]‐, [011]‐, and [111]‐poled Pb(Mg1/3 Nb2/3 )O3 ‐0.30PbTiO3 single crystals were studied by in situ polarized light microscopic driven by an antiparallel electric field. Orientation‐dependent electric field induced polarization and strain behaviors were investigated systematically. For [001]‐oriented crystals, only one‐step 71° switching occurred during the domain switching process, resulting in the appearance of stripe domain walls whose traces on (001) plane were along 45° or 135° with respect to [100] direction. But for [011]‐oriented samples, a two‐step 71° switching was observed during 109° switching and the projections of formed twin domain walls on the (011) plane are along 35.3° or 144.7° with respect to [01 1 ¯ ] direction. Moreover, a three‐step 71° switching was found during 180° switching in [111]‐oriented samples. It was demonstrated by the produced domain walls whose projections on the (1 1 ¯ 0) plane are along 35.3°, 90° or 160.6° with respect to [11 2 ¯ ] direction. The energetically motivated mechanism based on multistep polarization switching process was also proposed to explain the anisotropic domain switching paths. Our results provided a visualized observation on the ferroelectric domain switching process and also laid the solid foundations for controlling polarization order parameter in ferroelectric single crystals.